Gender aspects in victim behavior among adolescents - Valeeva, Roza A.; Litvinova, Natalia N.; Kulesza, Ewa M. (Special Education, 2016)
Research has been necessitated by the current situation in our society where the victim behavior is forming among children and adolescents and their gender roles are changing. To identify the causes of formation of victim behavior based on the analysis of gender characteristics of adolescents. The main research methods are the Bass-Darky questionnaire, the modified Freiburg Personality Inventory/Form B (FPI-B), a technique of study personal orientation that allow to identify the typical forms of respondents’aggressive behavior, some personality traits; to allocate four major types of personal orientation (humanistic, egocentric, sociocentric, negativistic). Deformation of gender stereotypes in modern society is reflected in the manifestation of victim behavior. Level of aggression, as one of the signs of victimization, is quite high both among boys and girls. Also among this category, adolescents with negativist personality orientation, in which a teenager does not accept himself or others, prevail. The research has resulted in some victim behavior features among adolescents. No clear gendered features have been identified that can be explained as the result of changing gender roles in contemporary society. The study has been identified some traits of victim behavior among adolescents, but no clear gendered features have been identified, it can be explained as the result of social changing gender in contemporary society, the masculinization phenomenon among the female population in particular.
Keywords: victim behavior; gender; victimization; masculinization